Design of ARCSI Learning Model with Scientific Approach for Teaching Mathematics in School - Usmadi Usmadi; Ergusni Ergusni (International Journal of Trends in Mathematics Education Research, 2018)
The study was aimed to obtain information regarding the design instructional of ARCSI learning model with the scientific approach for teaching mathematics in school. This learning model developed based on the learning conditions at Junior High School (SMP/MTs) in Bukittinggi City and Agam Districts of West Sumatera requiring a model of learning based on Islamic values, strategy in the motivation of ARCSI, and a scientific approach mandated in the curriculum of 2013. This learning model is designed for forming the character of learners in an Islamic way the learning process of mathematics that pleasant, and train students to think critically and comprehensively through a scientific approach. Synonymous ARCSI Learning Model with scientific approach, namely: (1) Attract the attention of learners by inviting praying/pleading to Allah Ta’ala, (2) Convey the purpose/benefit of learning and its application in daily activity, (3) The deliberations of the group to establish ukhuwah Islamiyah within the group, (4) a class discussion to establish ukhuwah Islamiyah classically, (5) Giving satisfaction to students with learning will make only because of Allah Ta’ala and the tradition of Prophet Muhammad SAW (6) Evaluate processes and the results of solving problems, and (7) Closing the learning by reading Hamdallah and greetings.